2005
DOI: 10.1021/ja0543090
|View full text |Cite
|
Sign up to set email alerts
|

(3 + 1) Assembly of Three Human Telomeric Repeats into an Asymmetric Dimeric G-Quadruplex

Abstract: We present an NMR study on the structure of a DNA fragment of the human telomere containing three guanine-tracts, d(GGGTTAGGGTTAGGGT). This sequence forms in Na + solution a unique asymmetric dimeric quadruplex, in which the G-tetrad core involves all three G-tracts of one strand and only the last 3′-end G-tract of the other strand. We show that a three-repeat human telomeric sequence can also associate with a single-repeat human telomeric sequence into a structure with the same topology that we name (3 + 1) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 48 publications
9
134
0
Order By: Relevance
“…In this case,the G 4 tract donates its last guanine residue (G9) to the second loop,t hereby preventing an adenine residue from occupying the first position of the loop.Anantiparallel fold with loop lengths of two,six, and two residues in the fold of s22 can be achieved with apropeller-diagonal-propeller or edgewise-diagonal-edgewise combination of loop types. Several structures in the presence of Na + ions have shown ap reference for edgewise over propeller-type loops, [26][27][28][29] presumably owing to the potential interaction of Na + cations in the outer G-quartets with the loop residues.…”
Section: Methodsmentioning
confidence: 99%
“…In this case,the G 4 tract donates its last guanine residue (G9) to the second loop,t hereby preventing an adenine residue from occupying the first position of the loop.Anantiparallel fold with loop lengths of two,six, and two residues in the fold of s22 can be achieved with apropeller-diagonal-propeller or edgewise-diagonal-edgewise combination of loop types. Several structures in the presence of Na + ions have shown ap reference for edgewise over propeller-type loops, [26][27][28][29] presumably owing to the potential interaction of Na + cations in the outer G-quartets with the loop residues.…”
Section: Methodsmentioning
confidence: 99%
“…(69) Zhang and co-workers have also reported the NMR structure of an asymmetric dimeric G-quadruplex in sodium solution from the three-repeat human telomeric sequence G 3 (T 2 AG 3 ) 2 . (57) This quadruplex is unique in that its G-quartet core involves all three G-tracts of one strand and only the terminal 3 0 -end G-tract of the second, although the arrangement of bases is very similar to that of the hybrid parallel/antiparallel intramolecular structure discussed above. The authors term this arrangement (3 þ 1) quadruplex assembly and speculate that it has the potential to participate in T-loop formation (Fig.…”
Section: The Intermolecular Human G-quadruplex Variantsmentioning
confidence: 93%
“…(55) In this setting, the quadruplex may represent an alternative to the T-loop structure (54) (Fig. 2Ai) or it may form an integral part of it (56,57) (Fig. 2Aii).…”
Section: In Vivo Evidence For G-quadruplexesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Peptide Nucleic Acid (PNA) is a synthetic mimic of DNA in which the negatively charged phosphate backbone is replaced by a neutral polyamide backbone, thus allowing it to hybridise in a sequence specific manner and with high affinity to either DNA or RNA. Recently, it has been shown that carefully designed G-rich PNA oligomers were also capable of forming PNAB 4 B quadruplexesP A recent NMR study reported an unprecedented structure for a DNA fragment of the human telomeric region containing three G-rich repeats, d(GGGTTAGGGTTAGGGT) in sodium solution.P 16 Here an asymmetric dimeric quadruplex was formed where the G-tetrad core involved all three G-tracts of one of the strands and the 3′-most G-tract of the second strand. The threerepeat sequence could also associate with a solitary G-rich unit d(GGGTTA) to form a bimolecular complex called the (3+1) assembly.…”
Section: Introductionmentioning
confidence: 99%